Comparative Analysis of the Support Capacity and Settlement of Bored Pile Foundations Using Manual Methods and Allpile Software: Case Study - Hidayatulloh, Syarif; Pascanawaty, Maya Saridewi; Hamdani, Hafiz; Fitrayudha, Adryan (Journal La Multiapp, 2025)
Foundations are structural elements that function to bear the load of a building and transfer it to the ground to a certain depth. Foundations must be designed so that the transferred load does not exceed the bearing capacity of the soil, as this can cause excessive settlement and lead to structural collapse. The purpose of this study is to determine the comparison of bearing capacity and settlement of bored pile foundations in the Poltekkes Kemenkes Mataram building using two approaches: the manual method and the Allpile software. The analysis was conducted based on secondary data obtained from the Detailed Engineering Design (DED), results of the Standard Penetration Test (SPT), and laboratory soil test results. The results of the manual Meyerhof method yielded an ultimate bearing capacity of 13,127.79 kN and a single pile settlement of 0.0455 m. The manual Reese and Wright method yielded an ultimate bearing capacity of 2,697.3453 kN and a single pile settlement of 0.0241 m. Meanwhile, the Allpile software calculation yielded an ultimate bearing capacity of 14,391.891 kN and a single pile settlement of 0.0027 m. All settlement values, both for single piles and groups, remain below the maximum permitted limit.